Monitoring and Management of the Palliative Care Patient Symptoms: A Best Practice Implementation Project - Coelho, Adriana (2022)
Background: In palliative care, symptoms are multiple and combined, evolving and changing, with a multidimensional character and multifactorial causes, and a high prevalence, negatively influencing the patient’s and family’s quality of life. Nurses who provide palliative care need to recognize and respond effectively to their patients’ symptoms. Methods: A project will be applied to implement the best practice in monitoring and managing palliative care patients’ symptoms. The Joanna Briggs Institute Practical Application of Clinical Evidence System (JBI PACES) and Getting Research into Practice (GRiP) audit and feedback tool will be used. The JBI PACES and GRiP framework for promoting evidence-based healthcare involves three phases of activity. First, a baseline audit. In a second phase, feedback will be given to the project team after the conclusion of the baseline audit report. Then, a third phase will be conducted as a follow-up audit. Conclusions: This project will improve the practice of the nursing team in monitoring and managing the symptoms of palliative care patients, positively influencing the quality of life of the patient and his family. The implementation and dissemination of this project could boost its replication in other centres.